Hubungan Paritas dan Usia dengan Kejadian Kek pada Calon Pengantin Wanita di Puskesmas Banjit Lampung - Wayan Ike Ulandari; Maryati Sutarno (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The incidence of CED is still quite high in women of childbearing age. This will have an impact on the pregnancy period if it is not treated immediately. There are many factors that cause CED, including the age and parity of the bride and groom. The prevalence of CED is 21.3% in pregnant women and 17.6% in Women of Childbearing Age (WUS). To study the relationship between parity and age with the incidence of CED among prospective brides at the Banjit Lampung Community Health Center in 2024. Analytical survey, with a cross sectional approach, the population in this study were all prospective brides at the Banjit Lampung Community Health Center from January to September 2024 as many as 111 people, with a random sampling technique with a sample size of 53 respondents, using data namely data secondary with a checklist sheet, analysis using chi square. From the results of univariate statistical tests, it is known that of the 53 prospective bride and groom respondents at the Banjit Lampung Community Health Center in 2024, it is known that as many as 19 (35.8%) experienced CED, as many as 48 (90.6%) had risk parity (nullipara/primipara), as many as 23 (43.4%) were at risk, namely 20 or 35 years old. From the results of the Chi Square test, there is a relationship between age and the incidence of CED in prospective brides at the Banjit Lampung Community Health Center in 2024, with a value of (ρ value = 0.000), OR value = 39.667, meaning prospective brides who are aged 20 years or 35 years 39,667 times more at risk of experiencing SEZ and vice versa. There is no relationship between parity and the incidence of KEK among prospective brides at the Banjit Lampung Community Health Center in 2024, with a value (ρ value = 0.147). it is hoped that health workers will have a relationship between age and the incidence of KEK in prospective brides, so that this research can be used as a reference in providing services to prospective brides, because the results of the research are theoretically in line with health regulations Law No. 16 of 2019 concerning the minimum age limit Marry.  Keywords: Parity, Age, KEK  ABSTRAK Masih cukup tingginya angka kejadian KEK pada wanita usia subur. Hal ini akan berdampak ke masa kehamilan jika tidak segera ditangani, banyak faktor yang mneyebabkan KEK antara lain usia dan paritas calon pengantin. Prevalensi  KEK sebesar 21,3% pada ibu hamil dan 17,6% pada Wanita Usia Subur (WUS). Untuk mempelajari hubungan paritas dan usia dengan kejadian KEK pada calon pengantin wanita di Puskesmas Banjit Lampung Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh calon pengantin wanita di Puskesmas Puskesmas Banjit Lampung dari bulan Januari s/d September 2024 sebanyak 111 orang, dengan teknik random samplling dengan jumlah sample 53 responden, memakai data yaitu data sekunder dengan lembar cheklist, analisis menggunakan chi square. Dari hasil uji statsitik univariat diketahui Dari 53 responden calon pengantin di Puskesmas Banjit Lampung tahun 2024 diketahui bahwa  sebanyak 19 (35,8%) mengalami KEK, sebanyak 48 (90,6%) memiliki paritas berisiko (nulipara/primipara),  sebanyak 23 (43.4 %) pada usia berisiko yaitu usia 20 atau 35 tahun. Dari hasil uji uji Chi Square Ada hubungan usia dengan kejadian KEK pada calon pengantin wanita di Puskesmas Banjit Lampung Tahun 2024, dengan nilai (ρ value = 0,000,), nilai OR=39,667 artinya calon pengantin yang mengalami usia 20 tahun atau 35 tahun lebih berisiko 39,667  kali akan mengalami KEK dan begitu pula sebaliknya. Tidak ada hubungan paritas dengan kejadian KEK pada calon pengantin wanita di Puskesmas Banjit Lampung Tahun 2024, dengan nilai (ρ value = 0,147). Diharapkan kepada petugas kesehatan dengan adanya hubunganumur dengan kejadian KEK pada calon pengantin wanita, sehingga dengan adanya penelitian ini dapat dijadikan acuan dalam memberikan layanan calon pengantin, karena dari hasil penelitian secara teori seiring dengan permenkes UU No.16 Tahun 2019 mengenai batas usia minimal menikah.  Kata Kunci: Paritas, Usia, KEK